What can the structure of the palm print tell us? - Sont Rahardja. (2012)
Biometric based palm print identification technique has been attracting a lot of attention in recent years and it has always been an area of interest for development. This is because palm print can be used to easily distinguish different people and it will remain unchanged unlike other body parts like the iris. The palm print is also harder to replicate compared to the finger print. Other than identification purposes, palm print is also traditionally used to predict the fortune of an individual. This fortune telling technique is commonly known as palm reading or palmistry, and has also been implemented into a fortune telling system.